A study of design performance of refurbishment projects in Malaysia - Ali, Azlan-Shah; Kamaruzzaman, S.N.; Zulkiflee, Abdul-Samad; Pitt, M.R. (Architectural Inst Japan, 2010)
The refurbishment sector has the potential to keep growing and contribute to the growth of total-Malaysian construction output. The increased number of obsolete and deteriorating buildings, coupled with the limited land for new development will contribute to increased demand for refurbishment works in Malaysia. However, the performance of refurbishment projects in most developed countries is unsatisfactory. One of the sources of unsatisfactory performance is related to design problems. This study analyses the variables that could be used for measuring design performance and reviews design performance of refurbishment projects in Malaysia. The study concludes that the design performance of refurbishment projects in Malaysia is used in three-quarters of refurbishment projects. The percentage of completeness of design before work starts on site was more than 80 percent. The additional construction cost attributed to design changes during the construction stage was more than 20 percent of the original estimated cost.